2022
DOI: 10.3389/fphys.2022.1080837
|View full text |Cite
|
Sign up to set email alerts
|

The des-Arg9-bradykinin/B1R axis: Hepatic damage in COVID-19

Abstract: Patients infected by the SARS-CoV-2 virus are commonly diagnosed with threatening liver conditions associated with drug-induced therapies and systemic viral action. RNA-Seq data from cells in bronchoalveolar lavage fluid from COVID-19 patients have pointed out dysregulation of kallikrein-kinin and renin-angiotensin systems as a possible mechanism that triggers multi-organ damage away from the leading site of virus infection. Therefore, we measured the plasma concentration of biologically active peptides from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
1
11
1
1
Order By: Relevance
“…Mendes et al using LC-MS/MS reported higher levels of Brad 1−8 alongside lower Brad levels in COVID-19 patient plasma compared to healthy controls. 35 In bronchoalveolar lavage fluids obtained from COVID-19 patients, Brad 1−8 and Brad 1−7 were reportedly increased with decreased Brad concentration using ELISA. 3 Our results are consistent with literature reports that dysregulation of the RAS−KKS may be responsible for symptoms experienced by COVID patients, supporting the move to therapeutically target these systems.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mendes et al using LC-MS/MS reported higher levels of Brad 1−8 alongside lower Brad levels in COVID-19 patient plasma compared to healthy controls. 35 In bronchoalveolar lavage fluids obtained from COVID-19 patients, Brad 1−8 and Brad 1−7 were reportedly increased with decreased Brad concentration using ELISA. 3 Our results are consistent with literature reports that dysregulation of the RAS−KKS may be responsible for symptoms experienced by COVID patients, supporting the move to therapeutically target these systems.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Also, severe disease conditions are characterized by difficulty in breathing, which may be related to enhanced production of Brad as well as other factors. Mendes et al using LC-MS/MS reported higher levels of Brad 1–8 alongside lower Brad levels in COVID-19 patient plasma compared to healthy controls . In bronchoalveolar lavage fluids obtained from COVID-19 patients, Brad 1–8 and Brad 1–7 were reportedly increased with decreased Brad concentration using ELISA .…”
Section: Results and Discussionmentioning
confidence: 98%
“…Perhaps lower pulmonary ACE2 is Covid 19 protective, but the downregulated ACE2 may be associated with higher levels of des-Arg9-bradykinin (see figure 5). Des-arg-BKN appears to be a prominent kinin in Covid-19 75 .…”
Section: Autoimmunity In Femalesmentioning
confidence: 94%
“…Perhaps lower pulmonary ACE2 is Covid 19 protective, but the downregulated ACE2 may be associated with higher levels of des-Arg9-bradykinin (see figure 5). Des-arg-BKN appears to be a prominent kinin in Covid-19 73 .…”
Section: Autoimmunity In Femalesmentioning
confidence: 94%